Épocas e extensões do período de convivência das plantas daninhas interferindo na produtividade da cultura do milho (Zea mays) - Kozlowski, L.a. (2009)
Q field experiment was carried out at the Gralha Azul Experimental Farm/PUCPR, in the municipality of Fazenda Rio Grande-PR, to evaluate the effect of different times and coexistence extension periods of weeds interfering in corn yield. The experiment was arranged in a complete randomized complete block design and the treatments in a 4x5+2 factorial, with four replications. The treatments were as follows: four initial weed control periods (0-0, 0-7, 0-14 and 0-21 DAE) and five restarted weed control periods until the harvest (28, 42, 56, 70 and 84 DAE) and two checks, weedy and weed-free. The experiment was carried out under a no-till system. The period prior to weed interference (PBWI), the start of the critical period of weed interference (CPWI) and the infesting community were evaluated. When the initial weed control period was 0-0 day, the PPWI was at 9 DAE of corn; however, with increasing initial weed control periods (0-7, 0-14 and 0-21 DAE) the period prior to weed interference inncreased in relation to 0-0 day of the initial weed control, evidencing the existence of PPWI-S of 17, 24 and 28 DAE of corn, respectively. Thus CPWI initiates at the end of PPWI-S, the period when weed control is indispensable to prevent a significant reduction in corn yield. Coexistance with the weeds throughout the crop cycle reduced yield in 15%, compared to the weed-free check. Nine species of seven botanical families were assessed in the infesting community. Reduced density and dry mass were verified in the weeds that coexisted with corn, compared to those that grew without it, thus evidencing a suppressive effect of corn over the infesting plants.